Dukungan Keluarga, Pengetahuan, dan Sikap Menurunkan Kecemasan Lansia dalam Pelaksanaan Vaksinasi COVID-19: Studi Cross Sectional - Heltty, Heltty; Nazaruddin, Nazaruddin (Jurnal Kesehatan Metro Sai Wawai, 2022)
Latar Belakang: Vaksinasi COVID-19 sebagai salah satu upaya pemerintah untuk menekan angka penyebaran COVID-19. Sementara, efek samping vaksinisasi COVID-19 menjadi salah satu penyebab kecemasan pada lansia. Dampak kecemasan dapat mempengaruhi lansia untuk memberikan keputusan untuk tidak melakukan vaksinasi COVID-19. Penting mengkaji kemungkinan faktor risiko kecemasan lansia yang diberikan vaksinasi COVID-19. Tujuan: Penelitian ini bertujuan untuk mengkaji beberapa faktor risiko kecemasan pada lansia, antara lain dukungan keluarga, pengetahuan, dan sikap dalam pelaksanaan vaksinasi COVID-19 di Wilayah Kerja Puskesmas Perumnas Kecematan Kadia. Hasil studi diharapkan dapat memberikan kontribusi alternatif pengembangan intervensi lansia yang cemas menghadapi vaksinasi COVID-19 berdasarkan faktor risiko. Metode: Penelitian ini adalah penelitian kuantitatif dengan menggunakan pendekatan cross sectional. Teknik pengambilan sampel menggunakan proportional random sampling dengan jumlah sampel sebanyak 57 responden lansia yang berusia 64 – 75 tahun. Data hasil penelitian dianalisis secara univariat maupun bivariat. Hasil: Penelitian menemukan hasil 82,5% lansia mengalami cemas untuk diberikan vaksinasi COVID-19. Faktor risiko pengetahuan, sikap dan dukungan keluarga mempunyai hubungan yang bermakna dengan kecemasan lansia melakukan vaksinasi COVID-19 (p-value > 0,05). Simpulan: Kecemasan lansia dalam vaksinasi COVID-19 dipengaruhi oleh beberapa faktor antara lain: pengetahuan, dukungan keluarga, dan sikap lansia terhadap vaksinasi COVID-19. Lansia agar tidak cemas hendaknya tidak terpengaruh isu-isu negatif tentang vaksinasi COVID-19 dan lebih mempercayai informasi dari pihak pemerintah tentang informasi vaksinasi COVID-19. Abstract: Family Support, Knowledge, and Attitudes Reduce Elderly Anxiety in the Implementation of COVID-19 Vaccination: Cross-Sectional Study Background: Background: Vaccination against COVID-19 is one of the government's efforts to reduce the spread of COVID-19. Meanwhile, the side effects of COVID-19 vaccination are one of the causes of anxiety in the elderly. The impact of anxiety can influence the elderly to make a decision not to vaccinate against COVID-19. It is important to examine possible risk factors for anxiety in the elderly given the COVID-19 vaccination. Purpose: This study aims to examine several risk factors for anxiety in the elderly, including family support, knowledge, and attitudes in carrying out the COVID-19 vaccination in the Working Area of the Perumnas Health Center, Kadia District. The results of the study are expected to provide an alternative contribution to the development of interventions for the elderly who are anxious about facing COVID-19 vaccination based on risk factors. Methods: This research is a quantitative study using a cross-sectional approach. The sampling technique used proportional random sampling with a total sample of 57 elderly respondents aged 64-75 years. Research data were analyzed using univariate or bivariate. Results: The study found that 82.5% of the elderly experienced anxiety about being given the COVID-19 vaccination. Knowledge, attitude, and family support risk factors have a significant relationship with the anxiety of the elderly doing the COVID-19 vaccination (p-value > 0.05). Conclusion: The elderly's anxiety about the COVID-19 vaccination is influenced by several factors, including knowledge, family support, and the attitude of the elderly toward the COVID-19 vaccination. So that the elderly are not worried, they should not be influenced by negative issues regarding COVID-19 vaccination and trust information from the government about COVID-19 vaccination information.